EFEKTIFITAS TERAPI AKTVITAS KELOMPOK STIMULASI PERSEPSI TERHADAP KEMAMPUAN MENGONTROL HALUSINASI PADA PASIEN HALUSINASI DI RSJ. PROF. HB. SA’ANIN PADANG TAHUN 2017 - Alber Tanjung; Amelia Susanti; Resi Puspita Sari (JIK-JURNAL ILMU KESEHATAN, 2017)
Hallucinations are one of the mental disorders in which the patient undergoes a perceptual sensory change. Data of mental disorder patients experiencing hallucinatory disorders as many as 856 people. Nurse RSJ. Prof Hb Saanin Padang has done TAK stimulation according to the procedure, but has not paid attention to client indication that can be included in TAK stimulation and do not follow up to client ability in control of hallucination. This study aims to determine the effectiveness of TAK perceptual stimulation on the ability to control hallucinations in patients hallucinations.This research uses Quasi Eksperimen design with Non Equivalent Control Group design. The subject of this research is the hallucination client. Sampling by purposive sampling with sample of 10 person control and 10 person intervention that fulfill inclusion criteria. The instrument used in the form of an interview questionnaire. Data processing is done computerized.The results showed that the average controlling ability of hallucinations in the control group on the pretest measurement was 11.20 and the posttest was 10.70. The mean controlling ability of hallucinations in the pretest intervention therapy group was 14.80 and posttest therapy was 18.60. Ineffective stimulation of perception to improve the ability to control hallucinations in Hallucinatory Patients in RSJ. Prof. Hb. Sa'anin Padang Year 2017.It was concluded that the activity of perceptual stimulation group was effective to improve the ability to control hallucinations in hallucinatory patients. It is expected that the RSJ nurses can improve the implementation of TAK perceptual stimulation by considering the indication of clients who can participate in TAK stimulation activities of perception and follow up on the client's ability to control the hallucinations. For the next researcher to be able to continue this research with different method and design to get more perfect result. Halusinasi adalah salah satu gangguan jiwa dimana pasien mengalami perubahan sensori persepsi.Data pasien gangguan jiwa yang mengalami gangguan halusinasi sebanyak 856 orang. Perawat RSJ. Prof Hb Saanin padang sudah melakukan TAK stimulasi sesuai prosedur, namun belum memperhatikan indikasi klien yang bisa diikut sertakan dalam TAK stimulasi dan tidak melakukan follow up terhadap kemampuan klien dalam mengontrol halusinasi. Penelitian ini bertujuan untuk mengetahui efektifitas TAK stimulasi persepsi terhadap kemampuan mengontrol halusinasi pada pasien halusinasi.Penelitian ini menggunakan desain Quasi Eksperimen dengan rancangan Non Equivalent Control Group. Penelitian diruang Melati dan Nuri RSJ. Prof. Hb. Sa’anin Padang bulan Februari 2016 – Agustus 2017. Subjek penelitian klien halusinasi diambildengan teknik purposive sampling berjumlah 10 orang kelompok kontrol dan 10 orang kelompok intervensi. Instrumen yang digunakan berupa kuesioner wawancara.Pengolahan data dilakukan secara komputerisasi.Hasil penelitian didapatkan bahwa rata-rata kemampuan mengontrol halusinasi pada kelompok kontrol pada pengukuran pretest adalah 11,20 dan posttestadalah 10,70.Rata-rata kemampuan mengontrol halusinasi pada kelompok intervensi pretest terapi adalah 14,80 dan posttestterapi adalah 18,60.TAK stimulasi persepsi efektif untuk meningkatkan kemampuan mengontrol halusinasi pada Pasien Halusinasi.Disimpulkan aktivitas kelompok stimulasi persepsi efektif untuk meningkatkan kemampuan mengontrol halusinasi pada pasien halusinasi. Untuk itu diharapkan kepada perawat RSJ dapat meningkatkan pelaksanaan TAK stimulasi persepsi dengan memperhatikan indikasi klien yang bisa ikut sertakan dalam kegiatan TAK stimulasi persepsi dan melakukan follow up terhadap kemampuan klien dalam mengontrol halusinasi. Bagi peneliti selanjutnya agar dapat melanjutkan penelitian ini dengan metode dan desain yang berbeda sehingga didapatkan hasil yang lebih sempurna.